Assessing the Dormant Bud Fruitfulness in Grapevines Spur for Yield Estimation - Poudel, Pragya; Dhakal, Ramila; Atreya, Nath; Sapkota, Rekha; Dahal, Kishor Chandra (Nepalese Horticulture, 2023)
Bud dissection is generally done to determine potential bud fruitfulness (average number of potential inflorescence primordia), can be used to predict the next season’s crop yield and make decision on pruning by analyzing fruitfulness of bud with respect to its position on cane/spur in order to achieve desired crop load. Comparison of potential inflorescence primordia with actual bunches with respect to each node give reliability on data from bud-dissection. The objective of this study was to detect potential inflorescence primordia and correlate it with observed bunches in vine. Bud dissection was carried out in a spur (having 4 buds from basal node towards apex) per vine of var. Himrod and var. Steuben from a vineyard of Warm Temperate Horticulture Centre, Kirtipur, Kathmandu, Nepal with the help of micro-dissection tools under stereo-microscope. It was revealed that cultivars ‘Himrod’ and ‘Steuben’ were both more prolific toward the buds located on distal nodes in comparison to buds situated on basal nodes; as a result, it was found that bud dissection can be used as a decisive tool for the detection of bud fruitfulness, thus for yield prediction and to develop appropriate management practice.